2022
DOI: 10.3390/jcm11216518
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of α-Klotho, Inflammation-Related Cytokines, and Mortality in Hemodialysis Patients

Abstract: It has been hypothesized that α-Klotho deficiency might contribute to chronic inflammation in patients with end-stage renal disease (ESRD), especially those on hemodialysis (HD). Serum Klotho levels by some authors are considered a potential predictor of cerebrovascular events. Therefore, we analyzed serum levels of α-Klotho with ELISA and inflammation-related cytokines in HD patients. Sixty-seven HD patients and 19 healthy people were recruited between November 2017 and June 2021. A Cytometric Bead Array (CBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…These differences are most likely due to a lower inflammation status in our cohort (CRP 0.43 mg/dL vs./8.46 mg/dL in Yu cohort) [ 37 ]. In addition, in another recently published study by Lisowska on 67 HD patients, the mean IL-1B levels were 1.75 pg/mL, much lower than Yu’s results and lower than the values from our cohort [ 38 ]. These differences may be in the context of several factors: inflammation and nutrition status, hemoglobin levels and anemia management, dialysis vintage, comorbidities and the number of patients.…”
Section: Discussioncontrasting
confidence: 92%
“…These differences are most likely due to a lower inflammation status in our cohort (CRP 0.43 mg/dL vs./8.46 mg/dL in Yu cohort) [ 37 ]. In addition, in another recently published study by Lisowska on 67 HD patients, the mean IL-1B levels were 1.75 pg/mL, much lower than Yu’s results and lower than the values from our cohort [ 38 ]. These differences may be in the context of several factors: inflammation and nutrition status, hemoglobin levels and anemia management, dialysis vintage, comorbidities and the number of patients.…”
Section: Discussioncontrasting
confidence: 92%
“…In summary, the complex pathophysiologic mechanisms suggested that Klotho downregulation is not merely an early biomarker for kidney damage, but also one of the principal complications of CKD and may play a pathogenic role in CKD progression [ 24 ]. Additionally, due to the complexity of the mechanism, whether serum Klotho reflects kidney function remains controversial in some studies [ 49 , 50 ], which requires high-quality research evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Further research has revealed that Klotho protein plays a crucial role in physiological and pathological processes such as cell apoptosis, cell proliferation, antioxidant defense, and in ammatory response. Speci cally, in the occurrence and development of atherosclerosis, Klotho protein may exert important protective effects through reducing oxidative stress, suppressing in ammatory response, and regulating lipid metabolism, among other pathways [11][12][13].…”
Section: Introductionmentioning
confidence: 99%